2004
DOI: 10.1002/hrdq.1113
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of participation and nonparticipation in job‐related education and training in Shenzhen, China

Abstract: In the fast-growing market-oriented economy of ShenzhenIn a global economy, maintaining organizational and individual competence has become a greater challenge than ever before (Hake, 1999). Education and training (hereafter, ET) is regarded as the primary means by which 389

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 23 publications
0
28
1
Order By: Relevance
“…Finally, several studies (n = 4) did not find differences between men and women (Garavan, Carberry, O'Malley, & O'Donnel, 2010;Lauber et al, 2010;Tharenou, 2001;Xiao & Tsang, 2004). Tharenou (1997), who conducted his study in the public sector, attributes the lack of difference between the participation of men and women to the regulations regarding gender equality in the public sector.…”
Section: Antecedents Of Employees' Participation In Work-related Learmentioning
confidence: 92%
See 1 more Smart Citation
“…Finally, several studies (n = 4) did not find differences between men and women (Garavan, Carberry, O'Malley, & O'Donnel, 2010;Lauber et al, 2010;Tharenou, 2001;Xiao & Tsang, 2004). Tharenou (1997), who conducted his study in the public sector, attributes the lack of difference between the participation of men and women to the regulations regarding gender equality in the public sector.…”
Section: Antecedents Of Employees' Participation In Work-related Learmentioning
confidence: 92%
“…Research has shown that the level of education is an especially important predictor of participation in formal training (e.g., Greenhalgh & Mavrotas, 1994;Ito & Brotheridge, 2005;Tharenou, 1997): Employees with a higher level of education tend to participate more in such training (e.g., Albert et al, 2010;Green, 1993;Montizaan et al, 2009;Tabassi & Bakar, 2009;Taylor & Urwin, 2001;Warr & Birdi, 1998;Xiao & Tsang, 2004). Tabassi and Bakar (2009) identified a low level of education as a barrier for participation.…”
Section: Antecedents Of Employees' Participation In Work-related Learmentioning
confidence: 98%
“…One recent study provided some empirical evidence on MD at the individual level in Shenzhen. Based on a study of 3475 employees in services and manufacturing sectors, Xiao and Tsang (2004) found that 31 percent of managers and 25 percent of professionals participated in training offered either by internal or external sources. Apparently, a Chinese colloquial, ‘recharging skills and knowledge’ ( zhishi chongdian ) has become a major theme among individual managers.…”
Section: The MD Policy Structurementioning
confidence: 99%
“…This suggests that there is little sample selection bias in the OLS estimate, in contrast to Xiao and Tsang (2004) who find that training participation depends on socio-economic characteristics of non-migrant workers. Note: Standard errors in parentheses, *, ** and *** denote 10%, 5% and 1% levels of significance respectively.…”
mentioning
confidence: 82%